Microstructural evolution and dry tribological properties of aluminium matrix composites reinforced with high-entropy alloys - Smith Salifu; Peter Apata Olubambi (International Journal of Sustainable Engineering)
This study investigates the microstructural evolution and dry tribological properties of aluminium matrix composites (AMCs) reinforced with high-entropy alloy (HEA). The reinforced AMCs were produced using the spark plasma sintering (SPS) technique with varying HEA contents (5%, 7%, 10%). Microstructural analysis of the reinforced composites showed enhanced interfacial bonding and minimal porosity. Tribological analysis of the reinforced AMCs revealed a significant reduction in wear rate and coefficient of friction with increased HEA content, thus, demonstrating the reinforcing effect of HEA particles in enhancing the wear resistance and durability of AMCs.